Taking Care : Lessons from Mothers with Disabilities. - Mason, Mary Grimley (University Press of America, 2012)
Taking Care, based on twenty-six interviews and other autobiographical narratives, challenges the negative stereotypes about mothers with disabilities. These women's stories tell of their successes despite the barriers they encounter from the society in which they live. This book will provide a significant model for all parents.